Which Lighting Option Is the Best for Photography in Rhinoplasty? - Fernández-Pellón, Rodrigo; Saghir, Meshari; Jaber, Ayman; Apaydin, Fazil (Facial Plastic Surgery, 2021)
Photography for preoperative analysis and follow-up is indispensable for the facial plastic surgeon. The use of strobe flash units, light-emitting diode (LED) lamps, and their position related to axis of the patient can affect the nasal contours and nasal measurements. The aim of this study was to compare the rhinoplasty pictures taken under three different lighting settings and two different positioning at 30- and 45-degree angles, and with direct measurements taken by caliper from the subjects. Standardized rhinoplasty pictures from 10 patients were taken in frontal view in a studio. These pictures were taken under three different lighting settings: built-in flash of the camera, two strobe flashes, and two LED continuous lights placed at 30 to 45 degree angles to the patient. All the pictures were uploaded to Rhinobase 2.0. In five subjects, direct measurements were done by using a Vernier caliper and compared with the computer measurements. In this study, when comparing the light sources and the angles without taking single flash into account, no relation was found between strobe lights at 30 and 45 degrees and between LED lights at 30 and 45 degrees regarding tip width, base bony width, dorsum width, interalar width, and nasal length. However, a statistically significant difference was found when the angle was changed from 30 to 45 degrees for tip width, interalar width and nasal length. The use of two LED continuous lights or two strobe lights in a studio setting has given similar results. Changing the angles of the light sources from 30 to 45 degrees affected only the tip width and the interalar width; otherwise the rest of the nasal measurements did not show any significant changes. The pictures taken at 45-degree angles to the subject showed the closest values to the direct measurements done on the patient.
Keywords: rhinoplasty; photography; lights